Inhibition of miR-21 by 3 `/5 `-serinyl-capped 2 `-O-Methyl RNA Interspersed with 2 `-O-(2-Amino-3-Methoxypropyl) uridine units - Nahar, Smita; Kotikam, Venubabu; Kumar, Vaijayanti A.; Maiti, Souvik (Nucleic Acid Therapeutics, 2016)
miRNAs are highly conserved class of small ncRNAs whose involvement in human pathophysiologies is extensively investigated. MiR-21 is a well established oncogenic miRNA whose deregulation plays a significant role in onset and progression of cancer. The need of novel approaches to downregulate miR-21 is rapidly expanding. Potent inhibition of miR-21 is achieved by chemically modified 2-O-methyl RNA oligonucleotide. The serinol capping at 3 and 5ends and the interspersed 2-O-(R-2-amino-3-methoxypropyl) uridine units enhance the nuclease resistance and efficacy of 2-O-methyl RNA for the inhibition of miR-21. This represents a simple and novel modification for developing oligonucleotide-based therapeutics.
Keywords: antagomirs; cancer; microRNA; noncoding RNA; oligonucleotides